Романтичні тенденції в поезії Якова Щоголева - Регуш, Ю.С. (Бердянський державний педагогічний університет, 2013)
Регуш Ю. C. Романтичні тенденції в поезії Якова Щоголева. – На правах рукопису. Дисертація на здобуття наукового ступеня кандидата філологічних наук за спеціальністю 10.01.01 – українська література. – Харківський національний університет імені В. Н. Каразіна Міністерства освіти і науки України, Харків, 2013. У дисертації проаналізовано поетичну спадщину Я. Щоголева у контексті романтичних тенденцій. Досліджується питання впливу на доробок письменника творчості представників харківської романтичної школи. Зазначається, що, створюючи свої власні поезії, митець використовував народні джерела та продовжив романтичні традиції української літератури першої половини ХІХ ст. Аналізуються провідні теми та мотиви поезії Я. Щоголева: фольклорні, історичні, релігійні та пейзажні мотиви, тема кохання, смерті та праці. Розглядаються у творчості поета романтичні образи русалки, козака, співця (кобзаря, лірника). Вивчається жанрова своєрідність лірики митця, часопросторова модель світу поезій, відзначаються особливості поетичного мовлення творів. Наголошується, що творчий доробок письменника займає вагоме місце в творенні української літератури. У висновках зазначається, що творчість Якова Щоголева була типовим явищем для української романтичної літератури ХІХ ст., але разом з тим і досить своєрідним, самобутнім проявом поетичного таланту харківського митця.
The romantic tendency of Jakov Schogolіv poetry
Regush U. The romantic tendency of Jakov Schogolіv poetry. – The Manuscript rights. The dissertation for receiving a scientific degree a candidate of Philology according to speciality 10.01.01. – Ukrainian literature. – Berdyansk state Pedagogical University. – Berdyansk, 2013. Manuscript. In the dissertation it is analyzed Jakov Schogoliv’s poetical heritage that is penetrated by romantic tendencies in the poet’s opinion. The emphasis is placed on the modern development of Ukrainian literary criticism which is characterized by increasing the interest to figures of writers, whose heritage is not yet completely returned to the reader. Literary critics provided a great value to the Jakov Schogoliv’s poetry and noted its important place in formation of Ukrainian literature of the XIX century. In work the characteristic of the world and Ukrainian romantic direction is given. Poetic activity of representatives of the Kharkov romantic circle is shined. The main lines which characterized creativity of poets romantics are marked out: the appeal to national poetic sources, expansion of communications of literature with folklore, development of Ukrainian language, the address to the Ukrainian subject and history, images of an inner world of the person, its experiences and sufferings, emergence of new motives and genres. Stages of formation of the identity of Jakov Shchogoliv are considered. Factors which influenced formation of esthetic views and a creative manner of the artist are noted. The literary way of the poet covers a considerable hour interval and has rather long pauses. Having begun the poetic activity in the 1840th years, the artist had finished it only at the end of XIX century. It is noted that despite a variety of subject and motives in creativity of the Kharkov writer, his poetic activity had a direct connection with the romantic direction of the Ukrainian literature of XIX century. The question of the influence on creativity of the writer of representatives of the Kharkov romantic school is investigated in the research. It is noted also that, creating own poetry and continuing romantic traditions Jakov Schogoliv used national sources. Influence of a national song, national narrative, fairy tales, notable in many artist's poems. It is noted also that, creating own poetry and continuing romantic traditions Jakov Schogoliv used national sources. In the thesis leading subjects and motives of poetry such as folklore, historical, Cossack, religious and landscape motives, subject of love, death and work subject have been analyzed. Subjects and motives which the poet developed during all his life are allocated. Romantic images of the mermaid, the Cossack, the singer (kobza player, lirnik) have been considered in the poet’s creativity. It is noted that J. Schogoliv's poetic inheritance is a skillful sample of romantic lyrics of XIX century, the poet's poems are created in the best traditions of the Ukrainian romanticism and in a direct connection with oral national creativity. The genre originality of lyrics of the artist is investigated; it is noted on the writer's special contribution to the development of a genre of landscape lyrics and a lyrical portrait. The temporarily spatial model of the world of verses of Jakov Schogoliv is characterized by a combination of historical, real and irreal space, and also historical, cyclic and linear hour model of works. The feature of poetic broadcasting of works and that the artist in the creative activity took a special place of laborious work on language of the verses has been noted. The special attention was paid by the artist to a poetic broadcasting of the works, relevance and accuracy of expressions, use of literary and folk song poetic means. Rhythmical and strophe creation of J. Schogoliv's poems is characterized by using of national and song and classical systems of versification. In conclusions it has been noted that the figure of the Kharkov romantic was not in view of all originality and isolation, wasn't ignored literary critics as during lifetime as after death. Jakov Schogoliv's creativity was the typical phenomenon for the Ukrainian romantic literature of the XIX century, but at the same time and rather peculiar, original manifestation of poetic talent of the Kharkov artist. All-round studying of Jakov Schogoliv 's poetic work gives the grounds to claim that works of the artist have come under influence of romantic tendencies which were characteristic for the Ukrainian and world romantic literature of the XIX century. The poet reinterprets subjects, motives and offenses which were inherent for representatives of the Kharkov romantic circle, creatively processes folklore sources, addresses to pages of native history, develops new lyric genres, improves a poetic broadcasting. Jakov Schogoliv's creativity had enriched the Ukrainian literature with skillful samples of the poetic word and had continued living romanticism in literature of the last decades of XIX century.
Keywords: романтизм; тенденції; мотиви; образи; жанрові різновиди; хронотоп; поетика